突破學校課程與教學的圍城：民眾教育的視角 Extend Beyond the Boundaries and Nature of Schooling: Perspectives of Public Pedagogy - 黃顯涵 Xian-Han Huang; 李子建 John Chi-Kin Lee (Higher Education Foundation, 2018)
二十一世紀世界各國課程改革浪潮此起彼伏，但實際的改革效果卻差強人意。本研究嘗試從民眾教育的視角再次思考對課程─此一基本概念的理解，探討課程對於學生在民主社會中建構公民身分的意義，並指出可從三方面對學校教學進行重構：課程資源的多維整合、課程場域的彈性延展、師生角色的動態轉換。 The 21st century has been witnessed to widespread global curriculum reform. However, the implementations of these reforms are hardly satisfactory. This paper attempts to reinterpret the meaning of schooling, curriculum and instruction from the perspective of public pedagogy, explore the function of curriculum for students to cultivate citizenship in a democratic society. Meanwhile, based on comprehensive analysis of previous literature, three approaches for reconstructing the schooling are suggested: Multi-dimensional integration of curriculum resources, fl exible extension of curriculum boundaries, and the dynamic role change between teachers and students.